Semiconductor Thermal Neutron Detector - Aoki, Toru; Miyake, Aki; Nakano, Takayuki; Koike, Akifumi; Morii, Hisashi; Mimura, Hidenori (UI Scholars Hub, 2013)
The CdTe and GaN detector with a Gd converter have been developed and investigated as a neutron detector for neutron imaging. The fabricated Gd/CdTe detector with the 25 mm thick Gd was designed on the basis of simulation results of thermal neutron detection efficiency and spatial resolution. The Gd/CdTe detector shows the detection of neutron capture gamma ray emission in the 155Gd(n, g)156Gd, 157Gd(n, g)158Gd and 113Cd(n, g)114Cd reactions and characteristic X-ray emissions due to conversion-electrons generated inside the Gd film. The observed efficient thermal neutron detection with the Gd/CdTe detector shows its promise in neutron radiography application. Moreover, a BGaN detector has also investigated to separate neutron signal from gamma-ray clearly.